The endometrium heals without fibrosis after menstruation: implications for uterine healing after cesarean delivery - Roberto Romero; Arun Meyyazhagan; Tinnakorn Chaiworapongsa; Emmanuel Bujold; Agustin Conde Agudelo; Sonia S. Hassan; Awoniyi Awonuga (Journal of Perinatal Medicine, 2026)
Abstract Background The human endometrium undergoes repeated cycles of bleeding, inflammation, tissue breakdown, and repair. Unlike most adult tissues, which heal through fibrosis, the endometrium restores its architecture and function after menstruation without scar formation. This capacity for scarless repair is essential for implantation, placentation, and reproductive success. Content Cesarean delivery creates a deep surgical injury that heals with fibrosis, altered extracellular matrix organization, and abnormal tissue architecture. Cesarean scar defects, cesarean scar pregnancy, and placenta accreta spectrum arise preferentially within these regions of abnormal healing. We examine the possibility that menstruation provides a physiologic model for understanding how the uterus restores tissue architecture without fibrosis. Summary The contrast between menstrual repair and post-cesarean healing raises a fundamental question: why does one form of uterine injury restore normal architecture while another leads to scar formation? Current discussions of cesarean closure focus largely on mechanical outcomes such as scar thickness and uterine rupture, whereas the biologic determinants of uterine healing remain poorly understood. Outlook A deeper understanding of the mechanisms that permit scarless repair of the endometrium may provide new opportunities to improve uterine healing after cesarean delivery and reduce the burden of infertility, adenomyosis, cesarean scar pregnancy, and placenta accreta spectrum.